Pengaruh IPM, Dana Desa dan Infrastruktur terhadap Pertumbuhan Ekonomi di 13 Kabupaten/Kota di Kalimantan Selatan - Ripandi, Akhmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The purpose of this research is the 13 districts/cities of the province of SouthKalimantan consisting of 11 districts ( Kotabaru, Banjar, Tanah Laut, Barito Kuala,Tapin, Hulu Sungai Selatan, Hulu Sungai Utara, Hulu Sungai Tengah, Balangan,Tabalong, Tanah Bumbu) and two cities (Banjarbaru, Banjarmasin). This study usesthe panel’s return data analysis ti the Fixed Effect Model. The results of this studyshow that the index of human development, village funds, and infrastructure at thesame time has a significant impact on economic growth. This study also indicates thatthe social development index is the dominant factor affecting economic growth indistricts/cities in South Kalimantan in 2012-2016.